Indonesian Lexical Interference in Madurese Speech at Mantu Traditional Events in Sumenep - Sulistiyono, Sulistiyono; Ridwan, M (Universitas Muria Kudus, 2023)
Masalah yang mendasari pengkajian interferensi terhadap tuturan bahasa Madura setidaknya ada dua hal yakni interferensi dapat merusak pelestarian tuturan bahasa Madura yang baik dan benar, dan dapat merusak tradisinya. Interferensi dalam tuturan bahasa Madura mencakup interferensi leksikal, fonologi, morfologi, dan sintaksis. Target kajian sebagai berikut: (1) memperoleh gambaran tentang interferensi leksikal dari kata dasar atau kata jadian yang berbentuk kata serapan, kata sapaan, kata ungkapan dalam bahasa Indoenesia yang terkait dengan maknanya terhadap tuturan bahasa Madura pada acara tradisi mantu di Sumenep; (2) memperoleh gambaran tentang sebab terjadinya interferensi leksikal dari kata dasar atau kata jadian tersebut. Hal ini, didasarkan pada kajian teori interferensi leksikal kata dasar dan kata jadian tentang kata sapaan, kata serapan, kata ungkapan (idiom) serta kaidah tuturan bahasa Madura yang baik dan benar. Kajian ini menggunakan pendekatan penelitian deskriptif-kualitatif dengan prosedur sebagai berikut. Sumber data yang digunakan adalah tuturan si petutur, informan, peristiwa, dan literatur dengan teknik perekaman tuturan, wawancara, observasi, dan dokumentasi. Kajian menghasilkan temuan dan pemberian makna terhadap adanya interferensi leksikal kata dasar dan kata jadian tentang kata sapaan, kata serapan, kata ungkapan (idiom) dari sejumlah petutur dalam pertuturan acara tradisi mantu. Terjadinya interferensi tersebut disebabkan minimnya perbendaharaan kata dasar dan kata jadian tentang tingkatan tuturan halus serta pemahaman penggunaaannya sehingga tidak mampu mewakilkan yang disampaikan. Hal ini dapat merusak kaidah tuturan bahasa Madura yang baik dan benar serta merusak kesakralan acara tradisinya. There are at least two problems that underlie the study of interference with Madurese speech, namely that interference can damage the preservation of good and correct Madurese speech and can damage its traditions. Bearing in mind, Madurese speech has a level of speech in which the term Madurese is called ondhagga bhasa. This is also because in general the Madurese are bilingual people who are able to master two or more languages. Interference in Madurese speech includes lexical, phonological, morphological, and syntactic interference. The targets of the study are as follows: (1) to obtain an overview of lexical interference from basic words or derived words in the form of loanwords, greeting words, idioms in the Indonesian language which are related to their meaning in Madurese speech at the in-laws tradition event in Sumenep; (2) obtain an overview of the causes of lexical interference from the root word or the derived word. This is based on the study of lexical interference theory of basic words and invented words regarding greeting words, borrowed words, idioms (idioms) and good and correct Madurese speech rules. This study uses a descriptive-qualitative research approach with the following procedure. The sources of data used are the speeches of the speakers, informants, events, and literature using speech recording techniques, interviews, observations, and documentation. The study resulted in findings and giving meaning to the existence of lexical interference from basic words and derived words regarding greeting words, borrowed words, idioms from a number of speakers in the speeches of the mantu tradition. The occurrence of this interference is caused by the lack of basic vocabulary and invented words regarding the level of fine speech and understanding of its use so that it is unable to represent what is conveyed. This can damage the good and correct norms of Madurese speech and damage the sacredness of its traditional events.